Framework to assess data exchange in transboundary waters - CGIAR Research Program on Water, Land and Ecosystems (2019)
Developed framework for assessing the strength of data exchange in transboundary waters and piloted it in 25 river basins. Blue Peace (Water Cooperation NGO) has indicated their interest in incorporating this framework into their index, and the framework has informed UNECE United Nations Economic Commission for Europe data exchange guidelines.